ICD-11 Trauma Questionnaires for PTSD and Complex PTSD: Validation among Civilians and Former Abducted Children in Northern Uganda - Dokkedah, Sarah; Oboke, Henry; Ovuga, Emilio; Elklit, Ask (Journal of Psychiatry, 2015)
ICD-11 is expected to introduce a new diagnosis of C-PTSD, along with a revision of the current PTSD diagnosis. Are the suggested diagnostic tools for PTSD and C-PTSD valid in a developing country? Method: The tools have been tested on former abducted and regular civilians in northern Uganda (n=314), who have been influenced by the civil war that lasted for more than two decades. Results: The prevalence of either PTSD or C-PTSD was 36.6% and PTSD and C-PTSD was further found to correlate with symptoms of depression, anxiety and somatic complaints. Conclusion: Based on its findings the study concludes that the ICD-11 tools for PTSD and C-PTSD both appear to be valid as suggested by both discriminant and convergent validation of the tools. However, future research can benefit from studying cultural aspects of these diagnoses.
Keywords: PTSD; C-PTSD; War; Abduction; Children; ICD-11